Motivasi, Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Sang Hyang Seri (Persero) - Tama, Irwanto Dwi; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This research aims to determine the influence of motivation, compensation and work discipline on the performance of PT employees. Sang Hyang Seri (Persero) in Sidenreng Rappang Regency, either partially or simultaneously. Using saturated sampling techniques, this research involved 39 employees as samples. The research results show that partially, work motivation (X1) and compensation (X2) have a positive and significant effect on performance, while work discipline (X3) has no significant effect. Simultaneously, these three variables have an influence on employee performance, with a calculated F value of 18.921 which is greater than the F table of 2.87 and a probability of 0.000 which is below the significant value of 0.05. This aim is to determine the influence of motivation, compensation and work discipline on the performance of PT employees. Sang Hyang Seri (Persero) in Sidenreng Rappang Regency, either partially or simultaneously. Using saturated sampling techniques, this research involved 39 employees as samples. The research results show that partially, work motivation (X1) and compensation (X2) have a positive and significant effect on performance, while work discipline (X3) has no significant effect. Simultaneously, these three variables have an influence on employee performance, with a calculated F value of 18.921 which is greater than the F table of 2.87 and a probability of 0.000 which is below the significant value of 0.05.